Firms' Inflation Expectations: New Evidence from France - Frédérique Savignac; Erwan Gautier; Yuriy Gorodnichenko; Olivier Coibion (Institute of Labor Economics (IZA), 2022)
Using a new survey of firms' inflation expectations in France, we provide novel evidence about the measurement and formation of inflation expectations on the part of firms. First, French firms report inflation expectations with a smaller, but still positive, bias than households and display less disagreement. Second, we characterize the extent and manner in which the wording of questions matters for the measurement of firms' inflation expectations. Third, we document whether and how the position of the respondent within the firm affects the provided responses. Fourth, because our survey measures firms' expectations about aggregate and firmlevel wage growth along with their inflation expectations, we are able to show that expectations about wages are even more condensed than firms' inflation expectations and almost completely uncorrelated with them, indicating that firms perceive little link between price and wage inflation. Finally, an experimental treatment indicates that an exogenous change in firms' inflation expectations has no effect on their aggregate wage expectations.
Keywords: E2; E3; E4; 330; expectations; rational inattention; surveys; firms